Ultrasound-assisted extraction of polyphenols from Lonicera japonica leaves and their α-glucosidase inhibition - Li, Gang; Bao, Chunming; Zhang, Hao; Bai, Lu (Frontiers in Nutrition, 2025)
IntroductionThe search for natural bioactive compounds that act as α-glucosidase inhibitors is a central focus in diabetes treatment research.MethodsThis study utilized ultrasonic-assisted extraction to optimize the extraction of polyphenols from honeysuckle leaves through response surface methodology (RSM). Enzyme inhibition and fluorescence quenching experiments were conducted to examine the inhibitory activity and binding behavior of the extracted polyphenols.ResultsThe results indicated that the optimal conditions for polyphenol extraction were as follows: ethanol concentration, 64%, liquid–solid ratio, 45 mL/g, ultrasonic power, 700 W, ultrasonic time, 6 min. Under these conditions, the yield of polyphenols from honeysuckle leaves was 9.16 ± 0.19%, which closely aligns with the predicted value of 9.18%. The total phenolic content of the polyphenol extracts was 20.6 ± 0.67%, with chlorogenic acid and luteoloside contents measuring 5.65 ± 0.40% and 2.51 ± 0.14%, respectively. The inhibitory effect of polyphenol extracts (IC50, 0.14 ± 0.01 mg/mL) on α-glucosidase was better than that of chlorogenic acid (IC50, 0.55 ± 0.02 mg/mL). Fluorescence quenching experiments indicated that the polyphenol extracts interact with α-glucosidase, resulting in alterations to the microenvironment of amino acid residues.DiscussionThis interaction can reduce the binding affinity between the substrate and α-glucosidase, thereby contributing to the objective of lowering postprandial hyperglycemia. Our research results can provide reference for the development and utilization of honeysuckle leaves.